(untitled) (Global Journal of Medical Research, 2024)
Objective: to evaluate the prevalence and factors associated with tooth loss according to their number and position in cancer patients in southern Minas Gerais, Brazil. Methodology: a cross-sectional study with a sample of 441 adults undergoing cancer treatment. The outcome was obtained by clinical evaluation of tooth loss, categorizing the participants into: (i) having functional dentition (FD) [presence of 20 or more teeth] without anterior losses; (ii) having FD with anterior losses; (iii) not having FD. Independent variables included socioeconomic situation, health-related habits, general and cancer-related health, oral health, and dental care.